IMPLEMENTASI NAÃVE BAYES PADA SISTEM INFORMASI PEMBAYARAN SEKOLAH BERBASIS WEB DI SEKOLAH MENENGAH KEJURUAN NEGERI 1 JOMBANG - Supriyanto, Supriyanto; Imam Agung, Achmad; Ali, Mahrus (Inovate, 2023)
The storage of all data, both in the form of information or documents, used to only use books that were stored manually in document storage cabinets, which of course needed more space, but since the development of technology now uses databases to store school payment data. This research was conducted at SMK Negeri 1 Jombang. The calculation process uses the naÃ¯ve Bayes method to classify each student transaction that is paid off and not yet paid off. The results of this study are in the form of a web-based school payment information system which is expected to facilitate transactions at SMK Negeri 1 Jombang, especially in the administration sector, and to classify every student transaction that is paid off and not yet paid off. The research aims to build a computerized system that can help process transactions. The research used the action research method. There are four stages in this research method, namely: planning, action, observation and reflection. From the accuracy test, the system that has been built is 100% accurate. Keywords: Information Systems, naÃ¯ve bayes, school payments